PEMBELAJARAN THINK-TALK-WRITE UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMETAAN DAN BILANGAN BULAT PADA MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS KANJURUHAN MALANG - Dewi Asmarani (Jurnal Inspirasi Pendidikan, 2012)
This study describes how the Strategy Think Talk Write (TTW) can be used to enhance students' understanding of the concept mapping and the set of integers. Application of communication based learning strategy Think-Talk-Write (TTW) is more emphasis on reading comprehension of students to construct their own knowledge. Lecturers only act as a motivator, facilitator and guide. Thus students can be more independent in the learning process.Â Keyword: Strategy Think Talk Write (TTW), Mapping and the set of integers